Formação continuada em Educação Matemática para professoras de Educação Infantil: contribuições para os saberes docentes e as práticas pedagógicas - Dias, Sandra Maria Soeiro (2024)
Is it necessary and possible to talk about learning and teaching Mathematics in Early Childhood Education? There are several answers to this question: some refute, some adopt schooling practices and others envision promising scenarios, considering that Early Childhood Education is made up of space and time situated in everyday life with relationships between adults and children, which can, through varied experiences, share knowledge and build a rich, happy and creative Mathematics Education. In this context, we list the following guiding question for the thesis: How can we characterize the Mathematics Education practices that are being constructed, through knowledge, conditions and possibilities, considering specificities of the pedagogical work carried out in a public early childhood education institution in the city of São Gonçalo do Amarante/CE? The general objective of the research was to investigate the discursive and practical paths of children and teachers in their relationships with Mathematics Education in Early Childhood Education in a public institution in São Gonçalo do Amarante/CE. The specific objectives were: i) interpret the trajectories of professionals who work in Early Childhood Education with a focus on concepts of children, childhood, pedagogical practice and Mathematics Education; ii) analyze the theoretical and practical processes shared in the daily life of Early Childhood Education with a focus on experiences with Mathematics Education; and iii) foster training paths with two Early Childhood Education teachers through theoretical-discursive discussions in systematic meetings and pedagogical practices shared in the daily life of an Early Childhood Education institution. We developed a research with an action and participation strategy with the research subjects: teachers and children from two Early Childhood Education classes (Infant 3 and 5). We use different techniques and instruments: direct documentation, field diary, interviews, direct and indirect observation, questionnaires and training meetings. The implementation of the research took place throughout 2022 and mid-2023, following three stages: i) opening path: consent and first impressions of the teachers about the research; ii) path of approximation: through observations and a training section, we built a path to strengthen relationships shared with teachers, fostering the participatory place in research as a teacher at the institution, highlighting the practices and daily life lived with activities and contexts, for the promotion of Mathematics Education; and iii) training path: continued training and planning of practices with teachers, which, in a participatory way, made it possible to document and interpret the processes experienced. During the paths, the teachers' mathematical knowledge is validated by their practice, seeking to interpret it from their own perspectives. In relation to the teaching knowledge analyzed throughout the research, we realized that content knowledge is relevant considering the specificities of Mathematics, between limitations and justifications in the practice itself, feeding on the teachers' pedagogical and existential knowledge. The shared construction favored theoretical, discursive and practical reflections in the daily life of Early Childhood Education, giving visibility to the processes, co-created by the emergencies and limitations of this daily life, placing us in a real context and giving new meaning to Mathematics practices with the experiences of children and teachers throughout the research.